The Effect Of The Corporate Social Responsibility (CSR) Program In Improving The Quality Of Education - Defretes, Ulya; Yusran, Husna Leila (International Journal of Education, Vocational and Social Science, 2023)
The objectives of this study are: (1) To measure the effect of the Basic Program in improving the quality of education at the Elementary School (SD) level in Dompu Regency, West Nusa Tenggara. (2) Measuring the effect of the school literacy program on improving the quality or quality of education at the elementary school (SD) level in Dompu Regency, West Nusa Tenggara. And (3) Measuring the effect of the school leadership program on improving the quality or quality of education at the Elementary School (SD) level in Dompu Regency, West Nusa Tenggara. This study used a quantitative approach using the SEM (Structural Equation Modeling) method using Microsoft Excel 2010, SPSS version 20.0, LISREL version 8.80 for data processing. The population in this study were school principals and teachers/educators totaling 133 people and the sample was taken using the total sampling method to take the entire population of 133 people. Methods of data collection using questionnaires and documentation. Based on the results of the analysis it can be concluded that (1) the Basic Program has proven to be influential in improving the quality of education at the Elementary School (SD) level in Dompu Nusa Tenggara Regency. (2) The school literacy program has an effect on improving the quality of education at the Elementary School (SD) level in Dompu Regency, West Nusa Tenggara. And (3) the school leadership program has an effect on improving the quality of education at the elementary school level in Dompu District, West Nusa Tenggara.